Infantile myofibromatosis treated by mandibulectomy and staged reconstruction with submental flap and free fibula flap: a case report - Alexandra Maby; Benoit Guay; François Thuot (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Infantile myofibromatosis is the most common benign fibrous tumor in infants. Three different types have been reported in the literature. The most commonly affected areas are the head, the neck and the trunk. Our patient showed a very high level of mandibular destruction resistant to all mandibular sparing treatment strategies requiring segmental mandibulectomy and complex reconstruction. Case presentation We describe a rare case of multicentric infantile myofibromatosis with mandibular bone destruction. The treatment required a succession of chemotherapy, a subtotal transoral resection and a hemi-mandibulectomy. The mandibular reconstruction was staged with initial bridging titanium plate with a submental flap, followed later by a fibula free flap. Conclusion Mandibular involvement by myofibromatosis is rare, and the extend of bone destruction and reconstruction make this case unique. To our knowledge, this is the only reported case of fibula free flap mandibular reconstruction in a patient with infantile myofibromatosis , as well as one of the youngest reported submental island flaps for any pathology. We describe the clinical presentation and management, including relevant imaging, histopathology, medical and surgical treatment as well as a review of relevant literature.